The Effect of Endorsement & Online Promotion In Social Media on Purchase Intention In Culinary Business (Case Study On UMKM In The City of Palembang) - Stella Ovinda; Zakaria Wahab; Isni Andriana; Diah Natalisa (International Journal of Social Service and Research, 2022)
This study aims to determine the effect of endorsements and online promotions on purchase intention in the MSME culinary business in Palembang City. This study uses the Theory of Planned Behavior. The total population in this study was 1.66 million respondents. The sampling method is through the Slovin formula with a total sample of 399 respondents. The data analysis technique used in this research is multiple linear regression. The results obtained are endorsements and online promotions have a significant positive effect on purchase intention in the MSME culinary business in the city of Palembang. Suggestions that can be given for further research are so that MSMEs are more selective in choosing the role of influencers who can be trusted, have culinary knowledge, are honest with the message conveyed, and can display culinary qualities that are easy to understand when doing online promotions on social media.  Further researchers are expected to add other variables such as celebrity endorsement variables, word of mouth, online advertising, brand image, discount framing, and so on.